2009
DOI: 10.1093/bja/aep175
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of ultrasound-guided transversus abdominis plane block in patients undergoing open appendicectomy

Abstract: Ultrasound-guided TAP block holds considerable promise as a part of a balanced postoperative analgesic regimen for patients undergoing open appendicectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
226
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(243 citation statements)
references
References 12 publications
8
226
0
9
Order By: Relevance
“…6). Compared with the control group, the TAP block reduced the 24-hr pain score 20,30,31,39,48,62 by 1.7 (95% CI, App/IS = appendectomy /inguinal surgery; CD = Cesarean delivery; CI = confidence interval; I 2 = heterogeneity; IAW = inside abdominal wall; TAP = transversus abdominal plane block; US = ultrasound -2.4 to -1.0; P \ 0.001) and 24-hr morphine consumption 30,39,62 by 20.4 mg (95% CI, -29.7 to -11.1; P \ 0.001) ( Table 2).…”
Section: Transversus Abdominal Plane Block In Appendectomy and Inguinmentioning
confidence: 92%
“…6). Compared with the control group, the TAP block reduced the 24-hr pain score 20,30,31,39,48,62 by 1.7 (95% CI, App/IS = appendectomy /inguinal surgery; CD = Cesarean delivery; CI = confidence interval; I 2 = heterogeneity; IAW = inside abdominal wall; TAP = transversus abdominal plane block; US = ultrasound -2.4 to -1.0; P \ 0.001) and 24-hr morphine consumption 30,39,62 by 20.4 mg (95% CI, -29.7 to -11.1; P \ 0.001) ( Table 2).…”
Section: Transversus Abdominal Plane Block In Appendectomy and Inguinmentioning
confidence: 92%
“…Similar findings have been reported by other researchers demonstrating TAP block to provide excellent pain relief in patients undergoing appendectomy. 2,3,5 Comparable VAS at 30 min (0.65±0.93 and 0.90±1.11) postoperatively in both the groups in our study is most likely due to the residual effect of intraoperatively administered pethidine and paracetamol.…”
Section: Discussionmentioning
confidence: 47%
“…This was similar to the study performed by Mc Donnell et al [4] in caesarean section delivery where VAS at rest and on movement was significantly low till 12 hours in patients who received TAP block with local anesthetic. Study performed by Niraj et al [8] in open appendicectomy and Neerja Bharti et al [12] in colorectal surgery also showed similar results.…”
Section: Discussionmentioning
confidence: 53%
“…Our study results are comparable with Dawlatly et al [7] who showed 55% decrease in opioid requirement after USG guided TAP block in laparoscopic cholecystectomy. Niraj et al [8] showed 45% decrease in opioid requirement with USG guided TAP block in open appendicectomy. John Carney, McDonnell et al [6] also showed 47% decrease in opioid requirement with TAP block after total abdominal hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation